2019
DOI: 10.1080/02656736.2019.1647358
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided lung metastasis ablation: a literature review

Abstract: Purpose: To review the available options of percutaneous ablation of lung metastasis. Methods: General indications, prognostic factors, and image guidance of percutaneous lung ablations were reviewed. Specificities, technical aspects, advantages and limitations of each technic were highlighted. Complications and follow up where also reviewed. Results: Image-guided, percutaneous ablation is of interest for patients with a limit number (<3-5) small metastases (<2-3 cm). Other predictive factors have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 72 publications
0
49
0
1
Order By: Relevance
“…In general, MWA is not recommended for tumors located near the hilum since a heat sink effect may decrease the local control rate and thermal destruction could increase the risk of bronchial fistula and hemorrhage . The study by Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, MWA is not recommended for tumors located near the hilum since a heat sink effect may decrease the local control rate and thermal destruction could increase the risk of bronchial fistula and hemorrhage . The study by Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…In general, MWA is not recommended for tumors located near the hilum since a heat sink effect may decrease the local control rate 25 and thermal destruction could increase the risk of bronchial fistula and hemorrhage. 26 The study by Zhang et al demonstrated that brachytherapy, despite many punctures, does not add the possibility of hemorrhage, 27 which has also been demonstrated by our study without hemorrhage requiring intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with radiotherapy and chemotherapy, RFA focuses exclusively on the tumor area without causing any damage to the normal surrounding tissue (37). In addition, compared with surgical treatment, RFA is a minimally-invasive method (38). In advanced lung cancers, RFA is extremely effective for palliative care (39); however, it induces several complications, including local recurrence, which severely affects the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Competing approaches use radiofrequency (RF) or microwave (MW) irradiation, high‐intensity‐focused ultrasound (HIFU) and cryotherapy. The reader is referred to recent reviews for detailed discussion of the pros and cons of these competing modalities . None has become the established method of choice for any particular application and often many of the same technical, biophysical, biological and clinical issues are involved as in PTT.…”
Section: Key Factors In Pdt and Pttmentioning
confidence: 99%